Discovery of males of Caligus grandiabdominalis Yamaguti, 1954 (Copepoda: Caligidae) parasitic on redbelly yellowtail fusilier Caesio cuning (Bloch, 1791) from Sabah, Malaysia, with a redescription of the female of the species - Yusuke Kondo; Sohei Tanaka; Susumu Ohtsuka; Aurelia Jackson; Thyviaah Ananthan; Fui Fui Ching; Balu Alagar Venmathi Maran; Panakkool Thamban Aneesh; Masato Nitta; Ko Tomikawa (The Plankton Society of Japan, The Japanese Association of Benthology, 2025)
Caligus grandiabdominalis was originally described from Indonesia based on adult females obtained from the redbelly yellowtail fusilier Caesio cuning, although it has not been subsequently reported. In this study, we describe the adult male of C. grandiabdominalis for the first time, along with a redescription of adult females, and present a molecular characterization based on materials collected from a fish market in Sabah, Malaysia, in 2022. Caligus grandiabdominalis is a member of the Caligus bonito group, with which it shares the following characteristics: (1) leg 4 three-segmented, (2) distal exopod segment of leg 4 with one outer and three terminal spines; (3) leg 1 with three welldeveloped setae along the inner margin of the distal exopod segment; and (4) a row of denticles present along the outer margin of the second endopod segment of leg 2. It can readily be distinguished from other species within the group by the absence of a sternal furca. The genital complex and abdomen of females were observed to differ in shape, which could be associated with the degree of maturation. In one of the females, the posterior corners of the genital complex were more conspicuously developed than in the original description. The genital complex and abdominal somites of the remaining three female specimens were not laterally expanded, consistent with the original description. COI sequence analysis revealed a perfect match for females, whereas the genetic distance between the sexes was 0.020. Consequently, molecular analysis revealed the examined individuals to be conspecific.